Pengambilan Keputusan Inovasi pada Adopter Pertanian Organik Sayuran di Desa Ciputri, Pacet, Kabupaten Cianjur - Ulfah, Maria; Sumardjo, Sumardjo (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
An organic farm continue to be disseminated to farmers, but until now still quite a lot of farmers who do not adopt organic farming. The farmer's decision to adopt or reject the adoption of organic farming of vegetables can be seen from the stage of the decision making process of innovation. This research was done in the village of Ciputri, subdistrict Pacet, Cianjur District. The purpose of this research is to analyze the decision-making innovations on organic vegetable farming adopter and the factors related to the decision making innovation in adopter organic farming of vegetables. This research uses census on the population of farmers who adopting organic farming of vegetables and continue to adopting. The results showed that the level of knowledge adopter of organic farming of vegetables included in the category of being the real factors related to the level of knowledge that is land area and the level of courage to take risks. At the level of persuasion including the high category with tangible factors related to the level of persuasion that is the level of conformance. At the implementation level adopter of organic farming of vegetables including the medium category with tangible factors related to the implementation level is the level conformity procedures.Keywords: adoption, knowledge level, persuasion level, implementation level-----------------------------------------------------------------------------------------ABSTRAKPertanian organik terus disosialisasikan kepada para petani namun sampai saat ini masih cukup banyak petani yang tidak mengadopsi pertanian organik. Keputusan petani untuk mengadopsi atau menolak adopsi pertanian organik sayuran dapat dilihat dari tahap proses pengambilan keputusan inovasi. Penelitian ini dilakukan di Desa Ciputri, Kecamatan Pacet, Kabupaten Cianjur. Tujuan penelitian ini adalah menganalisis pengambilan keputusan inovasi pada adopter pertanian sayuran organik dan faktor-faktor yang berhubungan dengan pengambilan keputusan inovasi pada adopter pertanian organik sayuran. Penelitian ini menggunakan metode sensus pada populasi petani yang mengadopsi pertanian organik sayuran dan tetap melanjutkan untuk mengadopsi. Hasil penelitian menunjukkan bahwa tingkat pengetahuan adopter pertanian organik sayuran termasuk pada kategori sedang dengan faktor yang berhubungan nyata dengan tingkat pengetahuan yaitu: luas lahan dan tingkat keberanian mengambil resiko. Pada tingkat persuasi termasuk kategori tinggi dengan faktor yang berhubungan nyata dengan tingkat persuasi yaitu tingkat kesesuaian. Pada tingkat implementasi adopter pertanian organik sayuran termasuk kategori sedang dengan faktor yang berhubungan nyata dengan tingkat implementasi yaitu tingkat kesesuaian prosedur.Kata kunci: adopsi, tingkat pengetahuan, tingkat persuasi, tingkat implementasi